Faktor-Faktor Yang Mempengaruhi Kesehatan Reproduksi Pada Remaja SMP Di Wilayah Kerja Puskesmas Tanjung Unggat Kota Tanjungpinang Kepulauan Riau - Redayanti Redayanti; Sri Muharni; Rachmawaty M.Noer (Prodi D3 Farmasi Politeknik Katolik Mangunwijaya, 2025)
The biggest problem faced by teenagers in Indonesia is adolescent reproductive health problems, including unwanted pregnancy (UTD), abortion, early marriage and marriage, STDs or STDs and HIV/AIDS (Marmi et al, 2020). The aim of this research is to determine the factors that influence reproductive health in junior high school adolescents in the Tanjung Unggat Community Health Center working area. This type of research is quantitative descriptive with a cross sectional approach. The sampling method in this research is total sampling or saturated sampling. The sample in this study consisted of 83 junior high school teenagers. Data collection methods and tools use questionnaires. The conclusion from the data analysis is that there is a relationship between knowledge and family support and reproductive health in junior high school adolescents in the Tanjung Unggat Community Health Center Working Area, Tanjungpinang City with a significant p value = 0.000 <0.05. Suggestions for health workers to provide education about adolescent reproductive health, so that adolescents avoid problems related to adolescent reproductive health.